Treatment of locally advanced rectal cancer with radiation therapy and preoperative chemotherapy - Luongo, Alvaro; Aguiar, Sergio; González Machado, Luis; Guerra, José; Michelenea, Carlos; Bisio, Hugo; Ruiz Liard, Claudio; Varangot, Mario; Wolman, Roberto; Kasdorf, Pedro; García, Silvia; Tasende, Blanca; et al. (Cirugía del Uruguay, 1993)
Colorectal cancer has a high mortality rafe in Uruguay Surgery alone has a local relapsing rafe of 13-26%. Preoperative irradia/ion has shown to improve the ressecability and the local management. The aim of this protocol is to decrease the rafe of local relapse, using preopeative raiotherapy (RT) and concomitan/ chemoterapy that enhances the RT effects, improving therefore the therapeutic ratio.